SPECIAL issue on transitions in public administration: comparative perspectives of Sweden and the United States
This special issue focuses on the transitions underway in public administration. The studies included here reveal certain similarities in the kinds of reform underway as well as some clear differences in the way these reforms have been put into policy and practices. The first four articles examines changes in the erea of industrial housing, and environmental policy using different theoretical frameworks but sharing a comon focus on the contribution andd, in turn policy responsiveness. The three remaining pieces look at issue related to the public work force. Despite significant ddifferences in the structure and responsibities of government in Sweden and the United States, a number of similarities are evident in
Keywords: Environmental Policy; National Administrative Agencies -- Sweden; National Administrative Agencies -- U.S.A.; Civil Service -- Salaries etc. -- U.S.A.; Civil Service -- Salaries etc. -- Sweden; Public Policy -- Sweden; Public Policy -- U.S.A.; Public Housing -- Sweden; Home Rule (Sweden); Housing -- Sweden; Public Administration -- Sweden